Rooftop Agriculture in the Urban Global South: The Experience of Johannesburg - Rogerson, Jayne M. (Modern Geográfia)
Urban agriculture is attracting a growing international scholarship. The objective in this article is to examine the organization and contemporary state of rooftop agriculture in Johannesburg, South Africa’s commercial heart and largest city. Current international scholarship on rooftop agriculture is overwhelmingly dominated by research on the experience of North American and European cities. Although urban agriculture has generated a considerable literature in the Global South and especially in Africa, only limited work exists on rooftop farming. This study draws together existing material on the South African record of rooftop agriculture. It is shown that Johannesburg hosts the largest cluster of rooftop farms which have been established mainly for social considerations with smaller numbers of projects for commercial reasons or the image-enhancement of businesses. The importance of partnerships for the establishment of projects emerges as a distinctive element of the Johannesburg inner-city experience. The challenges confronting the rooftop farming projects are investigated.